The 2025 M w 7.7 Mandalay, Myanmar, earthquake reveals a complex earthquake cycle with clustering and variable segmentation on the Sagaing Fault - Solene L. Antoine; Rajani Shrestha; Chris Milliner; Kyungjae Im; Chris Rollins; Kang Wang; Kejie Chen; Jean-Philippe Avouac (Proceedings of the National Academy of Sciences, 2025)
We use remote sensing observations to document surface deformation caused by the 2025 M w 7.7 Mandalay earthquake. This event is a unique case of an extremely long (~510 km) and sustained supershear rupture probably favored by the rather smooth and continuous geometry of this section of the structurally mature Sagaing Fault. The seismic rupture involved the locked portion of the fault over its entire depth extent (0 to 13 km) with a remarkably uniform slip distribution that averages 3.3 m, and an average stress drop of 4.7 MPa. No shallow-slip deficit is observed. The rupture extent challenges usual scaling laws relating earthquake magnitude, fault length, and slip. The fault ruptured along a known seismic gap that last ruptured in 1839 and tailed off into sections that ruptured during large earthquakes in 1930 and 1946. The amplitude and spatial distribution of fault slip in the 2025 event conform only approximatively to the slip-predictable model and the segmentation inferred from the fault geometry and past ruptures. Plausible sequences of earthquakes with variable magnitude, segmentation, and return periods, including events similar to the 2025 earthquake are produced in quasidynamic simulations using a simplified but nonplanar fault geometry. Based on this simulation, M w >7.5 events return irregularly with an interevent time of ~141 y on average and a SD of ~40 y. The simulation is consistent with the historical seismicity and with the maximum magnitude ~M w 7.9 and return period (~250 y) derived from moment conservation. Data assimilation into such simulations could provide a way for time-dependent hazard assessment in the future.